Dom Marcelo Pinto Carvalheira: a mística como práxis cristã - Santana Júnior, Marcelo Marques (2015)
This research aims to study the mystical phenomenon in its universal character, taking as its starting point the life of Don Marcelo Pinto Carvalheira, from his birth in 1928 until his episcopal appointment in 1975. The choice of Don Marcelo was given for recognition of a very important legacy for the Church of Brazil, that it was based on a deep spirituality and a sense of responsibility on the surrounding universe. Therefore, were analyzed theoretical references, testimonials and personal material of Don Marcelo use. The testimonies were collected from a questionnaire previously sent to respondents and spontaneous reports. Considering the ephemerality that lives the post-modern society and the lack of references that the gaps today's time have, look at the life of this great man, should serve not only intellectual source, but itinerary of life.